2017
DOI: 10.1017/s0022215117000664
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharyngofixation in cleft palate repair surgery on the development of chronic adhesive otitis media

Abstract: Pharyngofixation did not significantly alter the severity of long-term otological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…OME in patients with cleft palate, or without cleft lip, has been extensively investigated in recent years. 27 There remains debate over the optimal surgical technique and management strategies for cleft palate repair, particularly regarding their influence on middle ear function. 17 While consensus is not unanimous about the impact of primary palatoplasty on audiological outcomes, a significant body of research posits that palate repair can restore soft palate integrity, improve palatal muscle architecture, enhance eustachian tube function, and subsequently decrease the risk of OME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OME in patients with cleft palate, or without cleft lip, has been extensively investigated in recent years. 27 There remains debate over the optimal surgical technique and management strategies for cleft palate repair, particularly regarding their influence on middle ear function. 17 While consensus is not unanimous about the impact of primary palatoplasty on audiological outcomes, a significant body of research posits that palate repair can restore soft palate integrity, improve palatal muscle architecture, enhance eustachian tube function, and subsequently decrease the risk of OME.…”
Section: Discussionmentioning
confidence: 99%
“…OME in patients with cleft palate, with or without cleft lip, has been extensively investigated in recent years 27 . There remains debate over the optimal surgical technique and management strategies for cleft palate repair, particularly regarding their influence on middle ear function 17 .…”
Section: Discussionmentioning
confidence: 99%
“…We are unable to comment on this with our data, as many of the studies explicitly included or excluded cholesteatoma in patients with cleft palate and controls, therefore skewing our findings. Furthermore, while there is limited evidence concerning the effects of palatoplasty on cholesteatoma occurrence, 1 study found that supplementing palatoplasty with an inferior or superior pharyngeal flap did not decrease the risk of cholesteatoma 85 . Another study noted that adults with previously repaired submucous cleft palates were more likely to have cholesteatoma 86 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while there is limited evidence concerning the effects of palatoplasty on cholesteatoma occurrence, 1 study found that supplementing palatoplasty with an inferior or superior pharyngeal flap did not decrease the risk of cholesteatoma. 85 Another study noted that adults with previously repaired submucous cleft palates were more likely to have cholesteatoma. 86 Overall, while patients with cleft palate have an elevated risk of cholesteatoma, this study could not comment on their recurrence rates after tympanomastoidectomy as compared with control patients.…”
Section: Discussionmentioning
confidence: 99%